Surgical treatment of peptic ulcer (Surgical methods followed at Alasad university hospital in Lattakia) - Kanjarawe, Aktham; Alosh, Ali; Saied, Modar (Latakia University Journal -Medical Sciences Series, 2018)
This study included 79 pationts who complained from complications of peptic ulcer and were treated surgically in AlAsad University Hospital during the years between 2012-2016 . The percentage of every complication was: Perforation 65.8% hemorrhage 19% Gastric outlet obstruction 15.2% Precentage of males was 77.2% vs. 22.8% for females . The mean age for every complication was :46 years for perforation , 53 years for hemorrhage ,56 years for obstruction . The percentage of smokers among our patients was 83.5% .And NSAIDs users consisted 64.6% of our patients . The most common signs and symptoms : perforation :epigastric pain 100% - hemorrhage: fecal occult 86.7%- Gastric outlet obstruction :vomitings 100% The management of every complication was: In the cases of perforation , management was by only omental patch in 90.4% of cases , and by omental plus vagotomy and gastrojuejunostomy in 2% . And distal gastroctomy was used in 3.8% of cases, and laparscopy was used in 3.8% The management of hemorrhage was by overswing in 80% of pationts , and by Bilroth II IN 20% of pationts . Tke management of obstruction was by vagatomy and Jaboulay in 50%of cases , and by vagotomy plus gastrojuejunostomy in 33.3% of cases , and by Bilroth II in 16.7% of cases . معالجة مضاعفات القرحة الهضمية جراحيا" (الطرق الجراحية المتبعة في مستشفى الأسد الجامعي باللاذقية) شملت الدراسة 79 مريضا" عانوا من مضاعفات القرحة الهضمية وعولجوا جراحيا" في مشفى الأسد الجامعي باللاذقبة بين عامي 2012-2016 وقد كانت نسبة كل من المضاعفات كمايلي :الانثقاب 65.8% النزف 19% انسداد مخرج المعدة 15.2% بلغت نسبة الذكور 77.2% مقابل 22.8% للإناث متوسط أعمار المرضى حسب كل مضاعفة للانثقاب 46 سنة –للنزف 53 سنة – انسداد البواب ( مخرج المعدة) 56 سنة نسبة المدخنين بين مرضى العينة المدروسة كانت 83.5 % ، ونسبة المعالجين بمضادات الالتهاب اللاستيروئيدية كان 64.6% الأعراض والعلامات الأشيع : الألم الشرسوفي 100% - النزف : التغوط الزفتي 86.7%- ولانسداد مخرج المعدة : الإقياءات 100% - بالنسبة لتدبير المضاعفات كان مختلفا" حسب كل مضاعفة : ففي انثقاب القرحة كان التدبير الأشيع بالرقعة الثربية فقط بنسبة 90.4% ، وبالرقعة الثربية مع قطع المبهم الجذعي والمفاغرة المعدية الصائمية بنسبة 2 % ، وتم إجراء استئصال معدة بعيد بنسبة 3.8 % مع مفاغرة معدية صائمية بطريقة أوميغابراون ، كما تم إجراء الإصلاح بالتنظير بنسبة 3.8% . في حالات القرحة الهضمية النازفة كان التدبير الجراحي موزعا" بين خياطة القرحة بنسبة 80% وقطع المعدة بيلروثII بنسبة 20% ، وقد تم إجراء إضافي للخياطة توزع بين ميكوليكز الذي كان الأشيع ، وقطع المبهم الجذعي مع تصنيع البواب بطريقة جابولي في حالة واحدة ، والمفاغرة المعدية الصائمية في حالة واحدة أيضا"، وأجريت الخزعة من القرحة المعدية النازفة . في حالات الانسداد كان التدبير الجراحي الأشيع بقطع المبهم الجذعي مع تصنيع البواب بطريقة جابولي بنسبة 50% ، وتم تدبير33.3% من الحالات بقطع المبهم الجذعي والمفاغرة المعدية الصائمية ، و 16.7% من الحالات بقطع المعدة إعادة الاستمرارية بيلروث II